Neutrophil to Lymphocyte Ratio as a Predictive Factor of Unfavorable Outcomes in Traumatic Spinal Cord Injury: A Systematic Review and Meta-analysis - Peyrovinasab, Amirreza; Zarei, Hamed; Janmohamadi, Mahrokh; Fekri, Mehra; Tahmasbi Arashlow, Farzin; Ghorbani, Alireza; Gharin, Pantea; Soroush, Pardis; Safari, Saeed; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2025)
Introduction: There are a number of biomarkers connected to inflammation that affect spinal cord injury (SCI) outcomes. This systematic review and meta-analysis was conducted to evaluate the prognostic value of the Neutrophil-to-lymphocyte ratio (NLR) in patients diagnosed with traumatic SCI. Methods: Observational studies evaluating the association between baseline NLR and severity or neurological improvement in traumatic SCI patients were systematically identified using Medline, Embase, Scopus, and Web of Science databases on March 4, 2025. The risk of bias among the included studies was assessed using the National Heart, Lung, and Blood Institute (NHLBI) tool. A random-effects model was employed for meta-analyses. Effects sizes were reported as odds ratios (ORs) or standardized mean difference (SMD), along with their 95% confidence intervals (CIs). Results: Six retrospective cohort studies involving 1,564 participants were included, with five eligible for meta-analysis. Blood samples were collected within 72 hours of admission. Meta-analysis showed that patients without neurological improvement had significantly higher NLR values (SMD: 0.98; 95% CI: 0.08–1.87; I² = 94.36%). Additionally, elevated NLR was independently associated with no neurological improvement (adjusted OR: 1.12; 95% CI: 1.06–1.17; I² = 0.04%). Qualitative synthesis further indicated that higher NLR values were consistently associated with greater injury severity in acute traumatic SCI. Conclusion: Elevated NLR is associated with greater injury severity and poorer neurological recovery in patients with acute traumatic SCI. These findings suggest that NLR may serve as a useful early prognostic biomarker in the clinical assessment of mentioned patients.